Trapping intermediate MLCT states in low-symmetry Ru(bpy) - Cadranel, Alejandro; Oviedo, Paola S.; Pieslinger, German E.; Yamazaki, Shiori; Kleiman, Valeria D.; Baraldo, Luis M.; Guldi, Dirk Michael (Chemical Science)
The picosecond excited state dynamics of [Ru(tpm)(bpy)(NCS)]+ (RubNCS+) and [Ru(tpm)(bpy)(CN)]+ (RubCN+) (tpm = tris(1-pyrazolyl)methane, bpy = 2,2′-bipyridine) have been analyzed by means of transient absorption measurements and spectroelectrochemistry. Emissive 3MLCTs with (GS)HOMO(h+)-(GS)LUMO(e-) configurations are the lowest triplet excited states regardless of whether 387 or 505 nm photoexcitation is used. 387 nm photoexcitation yields, after a few picoseconds, the emissive 3MLCTs. In contrast, 505 nm photoexcitation populates an intermediate excited state that we assign as a 3MLCT state, in which the hole sits in a metal-centered orbital of different symmetry, prior to its conversion to the emissive 3MLCTs. The disparities in terms of electronic configuration between the intermediate and the emissive 3MLCTs have two important consequences. On one hand, both states feature very different fingerprint absorptions in transient absorption measurements. On the other hand, the reconfiguration is impeded by a kinetic barrier. As such, the conversion is followed spectroscopically and kinetically on the 300 ps timescale.
CRIS-Team Scopus Importer:2022-04-14